Students' Strategies in Translating Idioms at Eighth Semester of English Department Students in Universitas Negeri Padang - Fadhilah Muslimah; Havid Ardi (Journal of English Language Teaching, 2019)
The objective of this research is to know the strategies used by the students in translating idioms. This study used descriptive method. The data of this study are the 30 translated idioms found in the novel The Adventures of Tom.  The instruments of this study are the idioms translations test.  To gain the trustworthiness of the research, this research applies the validator and the assessors. The findings of this study reveal that out of 30 idioms, 251 cases were translated by paraphrasing, 5 cases were translated by Omission of the entire idioms, and 194 cases were translated by literal translation. The finding showed that paraphrase strategy is most commonly used in translating idioms as 55% besides 1% for omission and 43% for literal translation It means that there is a need of study idioms in the translation class or the improvements of the students in strategies in translating the idiomsKey words: translation, idiom, strategy